2002
DOI: 10.1037/0021-9010.87.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Work time, work interference with family, and psychological distress.

Abstract: Despite public concern about time pressures experienced by working parents, few scholars have explicitly examined the effects of work time on work-family conflict. The authors developed and tested a model of the predictors of work time and the relationships between time, work interference with family (WIF). and psychological distress. Survey data came from 513 employees in a Fortune 500 company. As predicted, several work and family characteristics were significantly related to work time. In addition, work tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
421
7
15

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 505 publications
(465 citation statements)
references
References 40 publications
22
421
7
15
Order By: Relevance
“…Therefore, we tested the hypothesis that: Kanungo (1982) reported that academics have high job involvement and that their work forms part of their core identity. Research indicates that highly job involved employees work longer hours (Eby et al, 2005;Major et al, 2002). Previous work in the Australian university sector has found that men report higher levels of job involvement than women (Winefield et al, 2008), however, this research included both academic and non-academic university employees and must therefore be interpreted with caution.…”
Section: Organisational Supportmentioning
confidence: 75%
See 3 more Smart Citations
“…Therefore, we tested the hypothesis that: Kanungo (1982) reported that academics have high job involvement and that their work forms part of their core identity. Research indicates that highly job involved employees work longer hours (Eby et al, 2005;Major et al, 2002). Previous work in the Australian university sector has found that men report higher levels of job involvement than women (Winefield et al, 2008), however, this research included both academic and non-academic university employees and must therefore be interpreted with caution.…”
Section: Organisational Supportmentioning
confidence: 75%
“…Major et al (2002) reported that work hours are strongly influenced by the organisational work hour expectations communicated to employees. Furthermore, research suggested that women are more negatively affected by long working hour expectations than are men (Posig & Kickul, 2004).…”
Section: Dependentsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to many reviews of the literature (see, for example, Sparks et al, 1997), the stress and fatigue that sometimes result from longer work hours can affect employee health and well-being. In addition, longer hours may affect work-family conflict, leading to further stress in both personal and professional settings (Major, Klein, and Ehrhart, 2002).…”
Section: Work and Organizational Characteristicsmentioning
confidence: 99%